Implementation of Total Quality Management (TQM) in the Learning Process at MAS KMI Diniyyah Puteri Padang Panjang - Nabilah Imamah Izazi; Sri Kartikowati; Syakdanur Nas (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
This study aims to determine the implementation of Total Quality Management (TQM) in the standard learning process at Madrasah Aliyah. The research used a descriptive qualitative approach at MAS KMI Diniyyah Puteri Padang Panjang. The application of TQM will be discussed using the Juran Trilogy concept, which consists of quality planning, quality control, and quality improvement—collecting data using interview techniques, observation, and documentation. The informants in this study were school principals, curriculum representatives, teachers, and students. Furthermore, they check the data's validity using the source triangulation method and triangulation. The results of the study found that: Quality planning in the learning process starts from setting learning process standards in the Madrasah work plan with the standards used, namely the 2013 curriculum and the QUBA curriculum; Quality control of the implementation of learning is carried out using project-based learning methods and learning evaluations that are not only educational values, but there are character assessment tools by the QUBA curriculum, and quality improvement in the form of monitoring, evaluation and follow-up activities of the learning process where schools carry out periodic evaluations through teacher meetings and evaluation of student learning outcomes, supervision activities, conducting training for teachers in competency improvement and training for students in forming character. This study concludes that MAS KMI Diniyyah Puteri Padang Panjang has implemented the characteristics of TQM, namely continuous improvement, education, and training conducted for students and teachers.